Design implications for interactive and analogue technologies supporting distance education: a longitudinal mixed-method study during the pandemic - Sousa, Duarte Luis (2022)
This study investigates COVID-19's impact on the education system by gathering data on how interactive and analogue technologies mitigated such disruption. It also analyses how and if educational approaches were modi fied during the pandemic. The procedures consisted of the analysis of evidence retrieved from three surveys delivered to three stakeholder groups: teachers, stu dents, and parents (N=215), crossed with an examination of a set of 5-week lon gitudinal interviews (30) with the same groups (N=6). The results of the analysis are used to derive a set of important design implications that: (1) highlight short comings of the distance education (DE) strategies used during COVID-19 and how they can be mitigated; (2) empower the stakeholders with innovative peda gogical approaches that information communication technologies can foster, thus optimising DE; (3) promotes positive learning experiences supported with scien tific evidence. Conclusions are derived from a collaborative reflection on the stakeholders' daily needs during unpredictable circumstances.